Dysphagia caused by a foreign body. Issue 11 (11th November 2003) - Hiorns, M P; Patwardhan, N; Spitz, L
Abstract : A boy with a long history of dysphagia attributed to neurological impairment was shown to have a large oesophageal foreign body. It had remained undetected for five years as a central lumen allowed the passage of liquids and semisolids. Foreign bodies must be excluded in children with dysphagia.